Pengaruh Konsistensi Cita Rasa Dan Kualitas Produk Terhadap Kepuasan Konsumen Pada Kacang Telor Tugu Lilin Penumping - Tania Oktavia Kristanto; Dika Puspitaningrum (JURNAL ILMIAH NUSANTARA, 2025)
This research aims to study and analyze the impact of taste consistency and product quality on the level of customer satisfaction with the product Kacang Telor Tugu Lilin Penumping, amid the significant growth of the snack industry sector in Indonesia. The research background emphasizes the importance of these components in shaping consumer behavior, where product quality and taste consistency often serve as key determinants in the food industry. Thus, this research helps us understand how customer satisfaction correlates with product quality. The method applied is a descriptive quantitative approach, with the population covering all consumers of the product. Data collection techniques were conducted through questionnaires that successfully gathered 98 respondents. Data analysis includes instrument tests (validity and reliability), classical assumption tests (such as normality, multicollinearity, and heteroscedasticity tests), multiple linear regression analysis, and hypothesis testing to examine the influence of independent variables. The research results indicate that taste consistency does not have a significant influence on consumer satisfaction, whereas product quality exhibits a clear and meaningful positive relationship. The implications of these findings are that producers need to prioritize improving product quality to enhance customer satisfaction levels, strengthen brand loyalty, and expand market share.